The depositional evolution and responses to controlling factors in the Permian Upper Urho Formation, Western Mahu Slope, Junggar Basin, NW China. Issue 3 (8th December 2021) - Shi, Yong; Yu, Jingfeng; Xu, Heng; Fang, Zhibin; Luo, Xudong; Wang, Zhiqiang; Lu, Jing; Tan, Dujuan; Wang, Jingqi; He, Naixiang
Abstract : The abundant petroleum reserves have been found in the Urho Formation in the past few years in western Mahu Slope, Junggar Basin. A great deal of studies has been carried out regarding tectonic evolution, sequence stratigraphy, reservoir prediction, and mechanism in the Urho Formation. However, little is known concerning the depositional evolution and associated controlling factors in the Upper Urho Formation. In this study, thin sections, cores, wireline logs, and seismic volumes are utilized to identify and describe sedimentary facies/microfacies, analyse mineral components and micro characteristics of microfacies, predict facies/microfacies distributions, and reveal depositional evolution and associated controlling factors. The results indicate the identification of eight sedimentary microfacies and the evolution of fan delta systems in Upper Urho Formation. In addition, depositional evolution of fan delta systems from bottom to top in Upper Urho Formation is characterized by retrogradation during lacustrine transgression period. The controlling factors, including tectonic activities along northwestern thrust fold belt and lacustrine fluctuations together exert influences over depositional evolution of regressive fan delta systems in Upper Urho Formation. Abstract : Comprehensive stratigraphic column from the Permian to Early Cretaceous in Mahu Depression, Junggar Basin.